2000
DOI: 10.1021/jp994339n
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Dimer Structures of the Heavier Alkaline Earth Dihalides:  A Density Functional Study

Abstract: Density functional theory has been applied to investigate the monomeric and dimeric dihalides of the heavier alkaline earth metals. Quasirelativistic pseudopotentials and large basis sets with uncontracted d (and f) polarization functions on the metals and correlation-consistent all-electron basis sets on the halogens were utilized. The monomers of SrF2, BaF2, and BaCl2 were found to be genuinely bent, while CaF2 and SrCl2, although also bent, have extremely flat potential energy surfaces and are better descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
53
2
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 47 publications
8
53
2
1
Order By: Relevance
“…We have found computationally in refs. [1] and [64] that, among the Group 2 binary dihalides, the rigid linear monomers (e.g., BeX 2 and MgX 2 ) strongly prefer the D 2h dimer geometry, while the monomers that are bent (e.g. BaF 2 and SrF 2 ) show a strong preference for the C 3v geometry.…”
mentioning
confidence: 97%
“…We have found computationally in refs. [1] and [64] that, among the Group 2 binary dihalides, the rigid linear monomers (e.g., BeX 2 and MgX 2 ) strongly prefer the D 2h dimer geometry, while the monomers that are bent (e.g. BaF 2 and SrF 2 ) show a strong preference for the C 3v geometry.…”
mentioning
confidence: 97%
“…A recent study [43], however, found that this is true only in those cases where the monomers are linear. It is well known by now, that only the dihalides of the lighter alkaline earth metals are linear [1].…”
Section: Alkaline Earth Dihalide Dimersmentioning
confidence: 90%
“…4,5 There have since been numerous investigations concerning the factors governing the propensity for linear versus bent geometries. 3,[6][7][8] Polarization and d-hybridization appear to play important roles. The ''dimer'' species M 2 X 4 have been computed to have many isomers, generally with two or more halogen atoms bridging the metal centers.…”
Section: Introductionmentioning
confidence: 99%
“…The ''dimer'' species M 2 X 4 have been computed to have many isomers, generally with two or more halogen atoms bridging the metal centers. 6 Salt clusters with a closed shell ionic framework and outer shell electrons, such as Na 2 F are termed excesselectron clusters. These radial clusters are suitable for spectroscopic investigation, because they possess bound-tobound optical transitions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation